An Evolutionary Approach towards PhD Educational System in Medical Sciences in Iran: a Systematic Review of Educational Models in the Worlds Leading Universities - Behnam Sadeghirad; Majid Fasihi Harandi; Ali-Akbar Haghdoost; Majid Fasihi Harandi; Azadeh Rooholamini (Kerman University of Medical Sciences, 2009)
Background & Objective : In this study we aimed to evaluate the status of Worlds leading universities in PhD students education and to compare it with Iranian universities applying the approach of educational status evaluation in a research based way   Methods: Using a systematic review all documents present in the webs and related links of universities of first 10 countries in Shanghais Academic Ranking of World Universities were systematically reviewed information related to PhD education was systematically collected and analyzed   Results : Reviewing 28 leading universities revealed that the educational model in educating PhD students in 22 of them was research based and the rest are using course based model Passing taught courses as an index in course based model is considered to be among minimum course requirements in most of the universities which are using research based model In cases where passing such courses is voluntarily a consultant professor plays a significant role in guiding the students in selecting and attending theoretical courses   Conclusion : Based on the above explanation and similar to other successful countries it seems that it is time to create various models for training postgraduate students to meet industrial needs With revisions in educational curriculums purposeful attempts should be made to solve possible problems and train people who meet countrys developmental needs in regards with the twenty year prospect